A STUDY ON POTENTIAL DRUG-DRUG INTERACTIONS AMONG PATIENTS ADMITTED UNDER DEPARTMENT OF MEDICINE IN A TERTIARY CARE HOSPITAL IN INDIA - Bandyopadhyay, Sanjib; Mitra, Kaushik; Bhaumik, Dipankar; Das, Saibal (Journal of Biomedical and Pharmaceutical Research, 2021)
Objective: This study was conducted to evaluate the potential drug-drug interactions (pDDIs) among patients admitted in a tertiary care hospital in India. Methods: This was anobservational and cross sectional study for 3 months. All the patients admitted in the general ward under Department of Medicine. Pre-structured proforma and patient’s charts were be used for data collection on the 2nd day of admission. For drug interactions, online ‘Medscape Drug Interaction Checker’ was used. Results: A total of 61 charts were screened. A total of 304 drugs with 57 different types were admitted to these patients (including all dosage forms and routes). The total number of pDDIs were 217, of them 69 were minor, 130 were significant and 18 were serious (including repetitions in different patients). There were 13 unique serious pDDIs. Conclusion: The incidence of pDDIs in our study was high. Controlled study to evaluate whether good clinical management of DDIs can reduce drug-related morbidity or mortality is needed. Keywords:Potential drug-drug interactions (pDDIs), adverse drug reactions (ADRs), poly-medication, hospitalization, pharmacokinetic and pharmacodynamics interactions.